Safety, pharmacokinetics, and pharmacodynamics of TG103, a novel long-acting GLP-1/Fc fusion protein after a single ascending dose in Chinese healthy subjects - Jin, Jiangli; Cui, Gang; Mi, Na; Wu, Wei; Zhang, Xin; Xiao, Chunyan; Wang, Jing; Qiu, Xueying; Han, Mai; Li, Ziyan; Wang, Lei; Lu, Tong; et al. (European journal of pharmaceutical sciences, 2023)
TG103 is a novel GLP-1/Fc fusion protein, developed for the treatment of type 2 diabetes and obesity. This trial was designed to assess the safety and tolerability, pharmacokinetics (PK) and pharmacodynamics (PD) profiles after single ascending dose of TG103 in healthy Chinese subjects. In this double-blind, randomized, placebo-controlled phase I study, Chinese healthy subjects were admitted consecutively to TG103 3 mg, 7.5 mg, 15 mg, and 22.5 mg group with 8 subjects per group and randomized in a 3:1 ratio to receive TG103 treatment or placebo. Following a single subcutaneous(s.c.) injections of TG103, safety and tolerability were evaluated and blood samples were collected for PK and PD analysis at the specified time-points. Overall, 32 healthy subjects were enrolled and completed the study. During the study, a total of 84 adverse effects (AEs) were reported in 25 subjects, all were mild or moderate and resolved spontaneously without intervention. The most common treatment related AEs in TG103 group were decreased appetite (41.7%), nausea, flatulence, elevated urinary β2-microglobulin, increased serum total bile acid (20.8% each), decreased high-density lipoprotein (16.7%), abdominal distension (12.5%). After a single s.c. administration of TG103 3–22.5 mg, the median Tmax was 36∼48 h, and mean t1/2 was about 147.16∼184.72 h. The mean Cmax for each group was 94.35±52.19, 337.67±56.71, 757.67±206.99, 1236.33±666.25 ng/mL, with AUC0-t of 14.93±7.67, 59.15±7.39, 91.79±20.41, 163.61±55.99 μg·h/mL, respectively. It showed a linear pharmacokinetic profile in the single dose of TG103 3 mg to 22.5 mg. Compared with placebo, fasting blood glucose decreased in all dose groups, most notably in the 15 mg group, which was consistent with the changes in blood glucose during OGTT, while 2-hour postprandial glucose decreased in all dose groups except 3 mg group. TG103 offers a potential option for hypoglycemic therapy with good tolerability and safety. ClinicalTrials.gov NCT03990090; registered 18 June 2019. [Display omitted]